Development of a Differentiated Learning-Based Chemical Bonding Teaching Module to Enhance Scientific Argumentation Skills - Wawan Tahir; Yuszda K. Salimi; Akram La Kilo; Lukman Abdul Rauf Laliyo; Astin Lukum; Masrid Pikoli (Jambura Journal of Educational Chemistry, 2026)
This study aimed to develop a differentiated teaching module to enhance students' scientific argumentation skills on chemical bonding material. The method used was Research and Development (R&D) with the 4D model (Define, Design, Develop, Disseminate). Validation results from experts showed that the developed differentiated teaching module was highly valid (92% and 94%), very practical (100% and 97%), and effective, with more than 80% of students achieving the minimum competency standard (KKM) and an average score of 88. The improvement in scientific argumentation skills was reflected in the average pre-test score of 64, which increased to 80 in the post-test. Specifically, the indicators of scientific argumentation showed improvement: claims increased from 62.9% to 75.4%, data from 66.3% to 84%, warrants from 67.8% to 82.1%, and backings from 68.4% to 79.4%. The increase in scientific argumentation scores from pre-test to post-test indicates that the developed teaching module was effective in helping students hone their argumentative skills. However, the ability to formulate claims and backings still requires reinforcement, as they demand a more complex understanding. Nevertheless, this improvement suggests that the differentiated teaching module created and implemented can strengthen students' scientific argumentation skills in understanding chemical bonding material, making it recommended for broader application, especially in science education.